Optimal energy and reserves scheduling through controllable charging and discharging a fleet of electric vehicles : doctoral thesis - Pavić, Ivan (I. Pavić; Faculty of electrical engineering and computing, 2021)
The increasing share of electric vehicles creates new challenges for both the power and the transport systems. The power system is affected at multiple levels, from distribution and transmission grid operation, through new balancing efforts, up to the long-term power system adequacy issues. To decrease the negative effect of electric vehicles on power system, uncontrollable charging can be replaced with smart charging concept (unidirectional or bidirectional controllable). Smart charging resembles charging (or discharging) in the periods when such action suits the power system. It could be in the form of energy arbitrage or provision of flexibility services. In this dissertation the focus is on the provision of balancing capacity and energy as flexibility services. Through dissertation tri main areas are processed which answer the following questions: can the smart charging positively affect the power system? How to increase the flexibility provision from electric vehicles towards the power system? How to approach the flexibility markets with adequate capacity, not jeopardizing technical feasibility and users' comfort?